Fish, Coral, and Sponge Assemblages Associated With Altiphotic and Mesophotic Reefs Along the Guánica Biosphere Reserve Continental Shelf Edge, Southwest Puerto Rico - García-Hernández, Jaaziel E.; Sanchez, Phillip J.; Hammerman, Nicholas M.; Schizas, Nikolaos V. (Frontiers in Marine Science, 2018)
The benthic and fish communities of the central portion of the Guánica, Puerto Rico shelf edge were studied to determine species abundance, distributions and species overlap between two depth stratifications, 20 m and 45 m, at eight sites. A total of 67 fish species belonging to 21 families were identified. Similar species richness estimates were observed between depths, though fish assemblage composition differed significantly, with observable changes in feeding guild contributions of herbivore and omnivore (20 m) to a deeper assemblage composed of piscivores and planktivores (45 m). Coral assemblages consisted of 31 species at 20 m and 11 species at 45 m, accounting for 17.0% (± 1.76 SE) and 2.6% (± 0.89 SE) benthic cover for the altiphotic and mesophotic surveys, respectively. The altiphotic and mesophotic coral reef communities support different scleractinian coral assemblages with minimal species overlap. Altiphotic surveys of sponges yielded a higher species richness than mesophotic, with 60 and 54 species respectively, and an overall total of 71 species identified from both depths, with 45 species overlapping (63.0%). The percent cover of sponges surveyed at altiphotic reefs was 9.0% (± 1.04 SE) while the percent cover of sponges surveyed at mesophotic reefs was 14.0% (± 1.96 SE). Our data show fish, coral, and sponge assemblages are differentiated between 20 and 45 m along the Guánica shelf edge offshore of the Guánica Biosphere Reserve. This study represents the first observations for species distributions of adjacent altiphotic and mesophotic coral reef habitats along the Guánica shelf edge, as well as provides an annotated species list of the local sponge fauna. Combined, these results highlight the need for continued environmental stewardship and conservation in the area.